224 EXCESSIVE TIME TO TREATMENT DELAY IN RURAL NATIVE AMERICANS PRESENTING WITH ACUTE MYOCARDIAL INFARCTION: TEMPORAL TRENDS 1999-2006. Issue 1 (1st January 2007) - Duarte, A. C.; June-Tsosie, A.; Sewell, J. L.; Malasky, B. R.; Ranger-Moore, J.; Cudilo, E.; Sanderson, P.; Freund, N. S.; Galloway, J. M.; Brody, E. A.
Abstract : Background: Acute myocardial infarction (AMI) is a leading cause of morbidity and mortality in Native American (NA) communities. Time to presentation in NA with AMI in a large national database is minimally longer than in the general US population. However, the sample studied does not reflect the largely rural population served by the Native American Cardiology Program (NACP) at the University of Arizona. This prospective study was designed to examine the time to treatment (T2T) of rural NA patients and any longitudinal trends in T2T over the past 8 years. Methods: Three hundred twenty-two NA patients with AMI were evaluated at rural facilities and transferred to NACP from February 1999 through June 2006. Data obtained included T2T (symptom onset to clinical presentation at initial treating facility) measured continuously for patients presenting within 12 hours and as a count of patients arriving after 12 hours. Three longitudinal trends were evaluated: T2T among patients arriving at < 12 hours and proportion of patients presenting < 6 versus > 6 and < 12 versus > 12 hours. Results: T2T information was available on 293 patients. The overall median and mean times to presentation were 360 and 572 minutes. Cox proportional hazards model suggested no significant changes in T2T by year ( p = .880) in the cohort presenting under 12 hours. Binary logistic regression indicated no significant changes in the proportions of patients coming in < versus > 6 ( p = .939) or < 12 versus > 12 ( p = .986) hours over the 8 years of the study. Conclusions: Based on the above data, time to presentation in rural NA patients with AMI is longer than nationally reported and has not improved in 8 years. This T2T delay places NA patients at risk for poorer outcomes and increased mortality. Public education about the importance of rapid clinical presentation and symptoms of AMI would reduce the burden of AMI in rural NA communities.